2010
DOI: 10.1186/1471-2407-10-91
|View full text |Cite
|
Sign up to set email alerts
|

Polysialic Acid Neural Cell Adhesion Molecule (PSA-NCAM) is an adverse prognosis factor in glioblastoma, and regulates olig2 expression in glioma cell lines

Abstract: BackgroundGlioblastoma multiforme (GBM) is the most aggressive and frequent brain tumor, albeit without cure. Although patient survival is limited to one year on average, significant variability in outcome is observed. The assessment of biomarkers is needed to gain better knowledge of this type of tumor, help prognosis, design and evaluate therapies. The neurodevelopmental polysialic acid neural cell adhesion molecule (PSA-NCAM) protein is overexpressed in various cancers. Here, we studied its expression in GB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
69
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(73 citation statements)
references
References 48 publications
1
69
0
Order By: Relevance
“…Notably, this correlation is observed regardless of histological grade of astrocytic tumor. Previously, it was reported that polysialic acid expression is highly correlated with a poor prognosis of astrocytoma (31,(43)(44)(45). These combined results indicate that HNK-1 glycan expression is an efficient and favorable prognosis marker for patients with astrocytoma.…”
Section: Discussionsupporting
confidence: 53%
“…Notably, this correlation is observed regardless of histological grade of astrocytic tumor. Previously, it was reported that polysialic acid expression is highly correlated with a poor prognosis of astrocytoma (31,(43)(44)(45). These combined results indicate that HNK-1 glycan expression is an efficient and favorable prognosis marker for patients with astrocytoma.…”
Section: Discussionsupporting
confidence: 53%
“…NCAM over-expression in tumour astrocytes leads to a significant decrease in their invasive behaviour (Edvardsen et al, 1994;Owens et al, 1998), whereas addition of polysialylated acid (PSA) on NCAM has been shown to facilitate glioma invasion (Suzuki et al, 2005). Finally, PSA-NCAM has been recently proposed as a biomarker for the prognosis of patients with glioblastomas (Amoureux et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…PolySia, therefore, is confined to a small subset of proteins, with NCAM being by far the most abundant carrier of polySia in most mammalian cells (Colley, 2010;Galuska et al, 2010;Hildebrandt et al, 2010). Although polySia is diminished in the majority of tissues during development, various tumours are known to re-express polySia on NCAM and high polySia levels have been correlated with malignant potential and poor prognosis of small cell lung carcinoma, neuroblastoma, glioblastoma, medulloblastoma and rhabdomyosarcoma (Scheidegger et al, 1994;Figarella-Branger et al, 1996;Glüer et al, 1998a;Glüer et al, 1998b;Hildebrandt et al, 1998;Tanaka et al, 2000;Daniel et al, 2001;Amoureux et al, 2010). In the developing nervous system, polySia is crucially involved in the migration of neuronal precursors (Ono et al, 1994;Hu et al, 1996;Chazal et al, 2000;Weinhold et al, 2005;Angata et al, 2007;Burgess et al, 2008) and modulates the responsiveness of oligodendrocyte precursor to chemotactic migration cues (BarralMoran et al, 2003;Zhang et al, 2004;Glaser et al, 2007).…”
Section: Introductionmentioning
confidence: 99%